PURWARUPA KAMERA PEMANTAU DENGAN KENDALI ISYARAT JARI BERBASIS PENGOLAHAN CITRA - , LINGGA ADITYA PRAYUDA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
In some kinds of Dental Unit, there is a camera involved by dentists which is called dental camera or is well-known as oral camera. Oral camera is functioned to clearly observe patientsâ teeth and is controlled by the dentist. It is held and its focus of lens is directed into the patientâs teeth area. In this research, will be made an alternate operating system from oral camera. A monitor webcam as the analogue of oral camera is supported by robotic arm. Then, webcam input is used to capture the image of hand. Next, the image is processed to identify the signal of the dentistâs fingers to finally control the arm of the robotic oral camera. The identification of fingersâ signal is accomplished by using method of separating object and its background. Colorâs range of the dentistâs glove is used as the reference in identifying hand. Colorâs model used in this research is HSV. Among 8 colors of gloves which is tested, blue comes out as the best color. A good quality of luminous intensity is gained from 100-125 lux of indoor light. Furthermore, the optimum distance between the webcam input and hand is 55-65 cm. Time response between initiation of fingersâ signal and movement of robotic arm is 0,5-0,7 seconds on average. Three fingers can be used to initiate fingersâ signal in capturing image from the oral camera. Through the result of this research are expected to facilitate in dentistâs practice, so that the dentist can operate oral camera without touching it directly anymore.